Land use changes and its consequences on moose habitat - Olofsson, Ida (2017)
Human land use can reduce the amount and quality of wildlife habitats. During recent years, a high moose calf summer mortality have been discovered on Öland. Öland is a predator-free island in Sweden that is dominated by agriculture and presence of humans and grazing livestock. Results from earlier studies indicate that the females are not in bad condition during autumn. However, suboptimal habitat use during winter and the fact that most calves died because of starvation and that they had not lactated, indicate that the females are in bad condition during late gestation. The time from that greenery has started to the start of the parturition, might not be enough for the females to get in condition to be able to lactate and raise a calf. To increase the knowledge about the human impact on moose habitat in an agricultural landscape, I have studied how the forest and agricultural land have change during the last decades in the municipalities Borgholm and Mörbylånga on Öland. Secondly, I have studied habitat selection during calving and compared female moose that successful raised their offspring with those that lost their offspring during summer. My results revealed an increasing trend for the area grazed alvar and a decreasing for area of attractive crops as oats and sugar beets. Number of livestock, especially cows showed an increasing trend in both municipalities. There was also shown an increasing trend for the area agricultural land that was utilized and at the same time there was no unutilized agricultural land in the end of the study period on the island. The part of the land classified as non-forest land was higher 2012 compared to 2000 in Borgholm, while it remained the same in Mörbylånga. The part classified as core forest, however, was higher in both municipalities 2012, while the part classified as edge, corridor and islet was lower. In the north, the females with surviving calf selected more optimal habitat in general than the females with non-surviving calf. In the more agricultural south, there were just two females that succeeded to keep a calf alive during the summer, which made the same comparison between females with surviving calf and females with nonsurviving calf difficult in the south. The females that did not succeed to raise their calf did not select poorer habitat than the two females with surviving calf. My results show that there has been an intensification of the agricultural land use on Öland and that the proportion of total forestland has decreased, which may have reduced the quantity and quality of forage for moose especially during winter. It also shows that a good selection strategy during calving is not enough for the females to succeed to raise their offspring, especially where resources is scarce. Land use change could be a factor together with other factors as warmer temperatures and earlier spring, contributing to the high moose calf mortality. But more research is needed to explore how other factors are influencing, for example intra- and interspecific competition. Based on my result, I suggest more research on moose habitats during spring in agricultural dominance landscapes and female moose ability to meet the growing need for energy during parturition and lactation.